Aerobic Fitness Level Among University Athletes During Movement Control Order in Malaysia - Awang, Mohd Aminur Izuan; Abdul Rahim, Norhazira; Abdullah, Nurul Fadhilah; Mohamad Shalan, Nor Aijratul Asikin (Jurnal Sains Sukan & Pendidikan Jasmani, 2022)
Aerobic fitness level is one of the important components to maintain and improve athletes' performance. Movement Control Order (MCO) is hypothesized to affect athletes in terms of sustaining their aerobic fitness level. The purpose of this present study was to identify the aerobic fitness level among university athletes during the MCO. Fifty university athletes (age: 19 – 26 years old) from Sultan Idris Education University (UPSI) had participated in this study. The athletes completed a CLINIMEX aerobic fitness questionnaire through Google Form to estimate their aerobic fitness level. As the result, the minimum and maximum values of aerobic fitness obtained from the 50 university athletes were 9 and 16 METs. The aerobic fitness level among university athletes overall was 10.89 ± 1.83 METs. The aerobic fitness level among university athletes for males was 11.01 ± 1.89 METs while for females 10.41 ± 1.56 METs. It has been identified that aerobic fitness level among university athletes during movement control order is at a vigorous-intensity activity that is 6.0 METs and above. In conclusion, high level of aerobic fitness among university athletes during MCO shows that despite the limitation of space and exercise equipment, they still involved in physical activity.